Beyond the traditional scope of translanguaging: Comparing translanguaging practices in Belgian multilingual and monolingual classroom contexts. (July 2018) - Rosiers, Kirsten; Van Lancker, Inge; Delarue, Steven
Abstract: This paper investigates the interactional behavior and the socio-pedagogical valorization of translanguaging practices of teachers and pupils in a multilingual and a monolingual classroom. By including the latter, we aim at expanding the scope of translanguaging research. Based on linguistic-ethnographic fieldwork, our analyses demonstrate differences in the nature of translanguaging practices: norm-breaking in the multilingual classroom versus turning back to the norm in the monolingual classroom. Translanguaging practices occur in the margin as well as in the centre of the classroom activity, with socio-emotional purposes in both classroom settings. Pedagogical goals, however, are only observed in the multilingual classroom. Highlights: Integration of a monolingual classroom to broaden the translanguaging scope. Translanguaging practices can be norm-breaking or imply a turning back to the norm. Translanguaging practices occur in the margins and centre of classroom activities. Translanguaging practices can serve a socio-emotional purpose. Pedagogical translanguaging goals only occur in the multilingual classroom.